2019
DOI: 10.5194/amt-12-169-2019
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in the Aerosol Robotic Network (AERONET) Version 3 database – automated near-real-time quality control algorithm with improved cloud screening for Sun photometer aerosol optical depth (AOD) measurements

Abstract: Abstract. The Aerosol Robotic Network (AERONET) has provided highly accurate, ground-truth measurements of the aerosol optical depth (AOD) using Cimel Electronique Sun–sky radiometers for more than 25 years. In Version 2 (V2) of the AERONET database, the near-real-time AOD was semiautomatically quality controlled utilizing mainly cloud-screening methodology, while additional AOD data contaminated by clouds or affected by instrument anomalies were removed manually before attaining quality-assured status (Level … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
572
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 877 publications
(702 citation statements)
references
References 98 publications
11
572
0
4
Order By: Relevance
“…In Version 2, when the raw count signal decreases below 10 for the 440‐nm channel, then all of the data for all channels in that spectral scan are eliminated to avoid significant bias in 440‐nm AOD from diffuse radiation in the instrument FOV (Sinyuk et al, ). In Version 3, a low signal check is applied to all channels independently and channels with sufficiently high signal (to avoid significant biases from diffuse in FOV) are retained when AE is sufficiently high (>1.2 for the 675‐ to 1,020‐nm range or >1.3 for 870–1,020 nm; Giles et al, ). Therefore, AOD values in the longer wavelengths are retained since for fine‐mode smoke the AOD deceases significantly as wavelength increases resulting in adequate signal for accurate AOD measurements in these wavelengths.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Version 2, when the raw count signal decreases below 10 for the 440‐nm channel, then all of the data for all channels in that spectral scan are eliminated to avoid significant bias in 440‐nm AOD from diffuse radiation in the instrument FOV (Sinyuk et al, ). In Version 3, a low signal check is applied to all channels independently and channels with sufficiently high signal (to avoid significant biases from diffuse in FOV) are retained when AE is sufficiently high (>1.2 for the 675‐ to 1,020‐nm range or >1.3 for 870–1,020 nm; Giles et al, ). Therefore, AOD values in the longer wavelengths are retained since for fine‐mode smoke the AOD deceases significantly as wavelength increases resulting in adequate signal for accurate AOD measurements in these wavelengths.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, there is a cloud screening check in Version 3 for cirrus that does not utilize temporal variance for cloud detection but rather relies on the sky radiances within 6° scattering angle of the Sun. If the angular slope in scattering angle of the measured sky radiances in the solar aureole is sufficiently steep then there likely are cirrus cloud crystals present (due to very strong forward scattering) and there is a threshold on this angular dependence for determining cirrus presence (Giles et al, ). This check is particularly important for the current study as Southeast Asian data have been shown to suffer from cirrus contamination (Chew et al, ).…”
Section: Instrumentation Data and Methodologymentioning
confidence: 99%
“…To accomplish this task, we follow similar procedures used in Hsu et al (2013) to infer surface reflectances by performing an atmospheric correction to the VIIRS TOA reflectances at blue (0.488 μm) and red (0.672 μm) bands using satellite measurements collocated with AERONET AOD data (to remove the aerosol contribution to the signal). The AERONET data used in this analysis are based upon the latest Version 3 Level 2 AERONET direct sun AOD (Giles et al, 2019), which included updates to calibration and cloud masking and, among other things, reduce issues where cirrus clouds are underscreened, and highly variable aerosol features over-screened, compared to previous AERONET data versions. As a result, 4 years (2012-2015) of cloud-screened VIIRS TOA reflectances and AERONET data over North America were compiled to develop the spectral relationship for each season.…”
Section: 1029/2018jd029688mentioning
confidence: 99%
“…This analysis uses the latest AERONET version 3 direct-Sun L2 (cloud-screened, post-deployment calibrated, and quality-assured; Smirnov et al, 2000) data products. Version 3 includes improvements to sensor characterization and cloud-aerosol discrimination over version 2 (Giles et al, 2019), particularly in the detection of stable optically thin cirrus cloud layers and rapidly evolving fine-mode aerosol plumes. The geolocation accuracy of some sites has also been improved.…”
Section: Aeronet Data Description and Matchup Protocolmentioning
confidence: 99%